Phase III, Randomized, Double-blind, Placebo controlled trial of Efficacy, Safety and Tolerability of Antiviral drug Umifenovir vs Standard care of therapy in non-severe COVID-19 patients. (February 2022) - Ramachandran, Ravishankar; Bhosale, Vivek; Reddy, Himanshu; Atam, Virendra; Faridi, MMA; Fatima, Jalees; Shukla, Vaibhav; Khan, Zaw A; Khan, Hana; Singh, Vikram; Negi, Mahendra Pal Singh; Srivastava, Mukesh; et al.
Highlights: Phase 3, Randomized, Placebo-controlled trial of Umifenovir against COVID-19 Unique dosage of 800mg BID was tested Statistically significant endpoints achieved for Mild-asymptomatic patients Umifenovir is efficacious for Mild-asymptomatic patients Abstract: Objective: To test efficacy, safety and tolerability of Umifenovir in non-severe COVID-19 adult patients. Methods: We carried out randomized, double-blind, placebo-controlled, multicenter, phase III trials involving adult (18-75 years), non-severe COVID19 patients, randomized 1:1 on placebo or Umifenovir (800 mg BID, maximum 14 days) respectively along with standard-of-care. The primary endpoint for Asymptotic-mild patients was time to nasopharyngeal swab RT-PCR test negativity. For Moderate patients, the average change in the ordinal scale from the baseline scores on the eight-point WHO ordinal scale was assessed. Results: 132 patients were recruited between 3 rd October to 28 th April 2021, of which 9 discontinued due to various reasons. In Mild-asymptomatic patients (n=82), we found that 73% patients in the Umifenovir arm were RT-PCR negative, while 40% patients in the placebo arm were negative (P=0.004) on day 5. However, in the moderate group (n=41), the WHO scores for the Umifenovir arm was not statistically significant (P=0.125 on day 3), while it was statistically significant in the Mild-asymptomatic group (P=0.019 on day 5). Conclusion: Umifenovir meets the primary and secondary endpoint criteria and exhibits statistically significant efficacy for Mild-asymptomatic patients. It is efficacious, safe and well-tolerated at the tested dosage of 800mg BID, maximum 14 days.